Gridiron Club (Washington, D.C.) records - Gridiron Club (Washington, D.C.)
Correspondence, writings, club records, membership books, autograph albums, dinner programs and menus, financial records, newspaper clippings, printed matter, scrapbooks, slides, photographs, and other records relating primarily to the club's annual dinner hosting members of the press, the U.S. president, and other elected officials and political figures. The dinner features humorous anecdotes concerning the statesmen, politicians, and elected officials.
Journalistic organization founded in 1885. Members represent major newspapers, news services, news magazines and broadcast networks.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Journalism -- Societies, etc; Journalists -- United States; Political satire, American; Politicians -- United States -- Anecdotes; Presidents -- United States -- Anecdotes; Statesmen -- United States -- Anecdotes; United States -- Officials and employees -- Anecdotes; United States -- Politics and government -- Anecdotes; Washington (D.C.) -- Social life and customs